ANATOMI DAN IDENTIFIKASI EMPAT BELAS JENIS KAYU DARI MALUKU - Y I Mandang (Jurnal Penelitian Hasil Hutan, 1986)
General and anatomical features  of fourteen   wood species from Maluku  were observed and described for  identification  purposes.  Except for  Heritiera littoralis Dryand  and Tarrietia riedeliana Oliv.,  all wood species could be distinguished  one from   the others based on anatomical characters. A  tentative  identification  key is presented.